Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the exact values of the given trigonometric expressions, we can use angle addition formulas for cosine.
1. Calculating \(\cos \left(\frac{5 \pi}{12}\right)\):
Let's break down \(\frac{5 \pi}{12}\) in terms of simpler known angles.
We know:
[tex]\[ \frac{5 \pi}{12} = \frac{\pi}{3} + \frac{\pi}{4} \][/tex]
We will use the cosine addition formula:
[tex]\[ \cos(A + B) = \cos A \cos B - \sin A \sin B \][/tex]
Here, \(A = \frac{\pi}{3}\) and \(B = \frac{\pi}{4}\).
We know the cosine and sine values for these angles:
[tex]\[ \cos \left(\frac{\pi}{3}\right) = \frac{1}{2}, \quad \sin \left(\frac{\pi}{3}\right) = \frac{\sqrt{3}}{2} \][/tex]
[tex]\[ \cos \left(\frac{\pi}{4}\right) = \frac{\sqrt{2}}{2}, \quad \sin \left(\frac{\pi}{4}\right) = \frac{\sqrt{2}}{2} \][/tex]
Substituting these values into the cosine addition formula:
[tex]\[ \cos \left(\frac{\pi}{3} + \frac{\pi}{4}\right) = \cos \left(\frac{\pi}{3}\right) \cos \left(\frac{\pi}{4}\right) - \sin \left(\frac{\pi}{3}\right) \sin \left(\frac{\pi}{4}\right) \][/tex]
[tex]\[ = \left(\frac{1}{2}\right)\left(\frac{\sqrt{2}}{2}\right) - \left(\frac{\sqrt{3}}{2}\right)\left(\frac{\sqrt{2}}{2}\right) \][/tex]
[tex]\[ = \frac{\sqrt{2}}{4} - \frac{\sqrt{6}}{4} \][/tex]
[tex]\[ = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
Thus,
[tex]\[ \cos \left(\frac{5 \pi}{12}\right) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
2. Calculating \(\cos \left(105^\circ\right)\):
We know that \(105^\circ\) can be expressed as \(60^\circ + 45^\circ\).
We use the same cosine addition formula:
[tex]\[ \cos (A + B) = \cos A \cos B - \sin A \sin B \][/tex]
Here, \(A = 60^\circ\) and \(B = 45^\circ\).
We know the cosine and sine values for these angles:
[tex]\[ \cos (60^\circ) = \frac{1}{2}, \quad \sin (60^\circ) = \frac{\sqrt{3}}{2} \][/tex]
[tex]\[ \cos (45^\circ) = \frac{\sqrt{2}}{2}, \quad \sin (45^\circ) = \frac{\sqrt{2}}{2} \][/tex]
Substituting these values into the cosine addition formula:
[tex]\[ \cos (60^\circ + 45^\circ) = \cos (60^\circ) \cos (45^\circ) - \sin (60^\circ) \sin (45^\circ) \][/tex]
[tex]\[ = \left(\frac{1}{2}\right)\left(\frac{\sqrt{2}}{2}\right) - \left(\frac{\sqrt{3}}{2}\right)\left(\frac{\sqrt{2}}{2}\right) \][/tex]
[tex]\[ = \frac{\sqrt{2}}{4} - \frac{\sqrt{6}}{4} \][/tex]
[tex]\[ = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
Thus,
[tex]\[ \cos (105^\circ) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
In summary:
[tex]\[ \cos \left(\frac{5\pi}{12}\right) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
[tex]\[ \cos (105^\circ) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
1. Calculating \(\cos \left(\frac{5 \pi}{12}\right)\):
Let's break down \(\frac{5 \pi}{12}\) in terms of simpler known angles.
We know:
[tex]\[ \frac{5 \pi}{12} = \frac{\pi}{3} + \frac{\pi}{4} \][/tex]
We will use the cosine addition formula:
[tex]\[ \cos(A + B) = \cos A \cos B - \sin A \sin B \][/tex]
Here, \(A = \frac{\pi}{3}\) and \(B = \frac{\pi}{4}\).
We know the cosine and sine values for these angles:
[tex]\[ \cos \left(\frac{\pi}{3}\right) = \frac{1}{2}, \quad \sin \left(\frac{\pi}{3}\right) = \frac{\sqrt{3}}{2} \][/tex]
[tex]\[ \cos \left(\frac{\pi}{4}\right) = \frac{\sqrt{2}}{2}, \quad \sin \left(\frac{\pi}{4}\right) = \frac{\sqrt{2}}{2} \][/tex]
Substituting these values into the cosine addition formula:
[tex]\[ \cos \left(\frac{\pi}{3} + \frac{\pi}{4}\right) = \cos \left(\frac{\pi}{3}\right) \cos \left(\frac{\pi}{4}\right) - \sin \left(\frac{\pi}{3}\right) \sin \left(\frac{\pi}{4}\right) \][/tex]
[tex]\[ = \left(\frac{1}{2}\right)\left(\frac{\sqrt{2}}{2}\right) - \left(\frac{\sqrt{3}}{2}\right)\left(\frac{\sqrt{2}}{2}\right) \][/tex]
[tex]\[ = \frac{\sqrt{2}}{4} - \frac{\sqrt{6}}{4} \][/tex]
[tex]\[ = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
Thus,
[tex]\[ \cos \left(\frac{5 \pi}{12}\right) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
2. Calculating \(\cos \left(105^\circ\right)\):
We know that \(105^\circ\) can be expressed as \(60^\circ + 45^\circ\).
We use the same cosine addition formula:
[tex]\[ \cos (A + B) = \cos A \cos B - \sin A \sin B \][/tex]
Here, \(A = 60^\circ\) and \(B = 45^\circ\).
We know the cosine and sine values for these angles:
[tex]\[ \cos (60^\circ) = \frac{1}{2}, \quad \sin (60^\circ) = \frac{\sqrt{3}}{2} \][/tex]
[tex]\[ \cos (45^\circ) = \frac{\sqrt{2}}{2}, \quad \sin (45^\circ) = \frac{\sqrt{2}}{2} \][/tex]
Substituting these values into the cosine addition formula:
[tex]\[ \cos (60^\circ + 45^\circ) = \cos (60^\circ) \cos (45^\circ) - \sin (60^\circ) \sin (45^\circ) \][/tex]
[tex]\[ = \left(\frac{1}{2}\right)\left(\frac{\sqrt{2}}{2}\right) - \left(\frac{\sqrt{3}}{2}\right)\left(\frac{\sqrt{2}}{2}\right) \][/tex]
[tex]\[ = \frac{\sqrt{2}}{4} - \frac{\sqrt{6}}{4} \][/tex]
[tex]\[ = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
Thus,
[tex]\[ \cos (105^\circ) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
In summary:
[tex]\[ \cos \left(\frac{5\pi}{12}\right) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
[tex]\[ \cos (105^\circ) = -\frac{\sqrt{6}}{4} + \frac{\sqrt{2}}{4} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.